Identification of species on the basis of histomorphometrical study of compact bone - UPPAL, VARINDER; BANSAL, NEELAM; ANURADHA, ANURADHA (The Indian Journal of Animal Sciences, 2015)
The study was conducted on femur of human, cattle, buffalo, horse, dog, deer and poultry birds. The tissues were collected from mid shaft (diaphysis) of femur, decalcified, processed and paraffin section were cut. The cut sections were stained with hematoxylin and eosin, Masson's trichrome, periodic acid Schiff and alcian blue. The species can be identified on the basis of absence of plexiform bone in humans and its presence in animal bone and where plexiform bone is not present, the histomorphometry (Haversian system diameter and Haversian canal diameter) plays an important role in identification. Such type of study should be expanded more so that this data can be applied in forensic science.